Healing, Pain and Function after Midshaft Clavicular Fractures: A Systematic Review of Treatment with Immobilization and Rehabilitation. Issue 4 (25th March 2019) - Catapano, Michael; Hoppe, Daniel; Henry, Patrick; Nam, Diane; Robinson, Lawrence R.; Wasserstein, David
Abstract : Objective: To systematically evaluate the scientific literature examining the efficacy of nonoperative management for midshaft clavicular fractures, specifically looking at the effect of immobilization and/or functional rehabilitation. Type: Systematic review. Literature Survey: MEDLINE (PubMed), EMBASE, CINAHL databases were searched. Methodology: Inclusion criteria included adult patients enrolled in a controlled study evaluating bony healing, pain and/or function‐related improvements after a strict nonoperative treatment plan for management of midshaft clavicle fractures. Synthesis: A total of 10 articles were included in the study. Only four studies contained level I evidence; four studies were prospective case series without a control, and one was a retrospective case series without a control. Half of studies used a strict immobilization period, and most utilized a period of functional rehabilitation. There were no direct comparisons between rehabilitation protocols. Studies without a strict immobilization period had a nonunion rate of 5% to 24% and residual pain in 35% to 83% of patients compared to studies with a strict immobilization period with a nonunion rate of 3% to 29% and residual pain in 14% to 49% of patients. Studies including functional rehabilitation protocol reported functional as measured by the Constant Shoulder Score of 87.8 to 96, out of a maximum of 100 representing no functional limitations, and nonunion rates of 12% to 25% compared to 81 to 85 and 3% to 29% in those without a rehabilitation protocol. Conclusions: No studies directly examine the effect of immobilization and functional rehabilitation on clinical outcomes for midshaft clavicular fractures. Future studies are needed to better elucidate the most effective treatment. Level of Evidence: I